Tribonacci Numbers Close to the Sum 2^a+3^b+5^c - Irmak, Nurettin; Szalay, László (Mathematica Scandinavica, 2016)
We show that there are exactly 22 solutions to the inequalities \[ 0T_n-2^a-3^b-5^c10, \] where T_n denotes the n^th term (n0) of the Tribonacci sequence, and 0a,bc are integers. All the solutions are explicitly determined.